Stereotypic morphology of glutamatergic synapses on identified muscle cells of Drosophila larvae - Johansen, J (J Neurosci, 1989)
The distribution and morphology of glutamatergic synapses on Drosophila bodywall muscle fibers were examined at the single-synapse level using immunocytochemistry and electrophysiology. We find that glutamate- immunoreactive motor endings innervate the entire larval bodywall musculature, with each muscle fiber receiving at least one glutamatergic ending. The innervation is initiated at stereotyped locations on each muscle fiber from where moderately branched varicose nerve processes project over the internally facing muscle surface. Individual muscle fibers have distinct stereotypic patterns of nerve endings that occupy characteristic regions on the cell surface. The muscle-specific branching pattern of motor endings is reiterated by segmentally homologous fibers. Two morphological types of innervating nerve processes can be distinguished by their bouton size distributions: (1) Type I processes, which have localized branching and a broad size distribution of relatively large varicosities ranging up to 8 microns (mean diameter, 3.1 +/- 1.6 microns; +/- SD, n = 521), and (2) thinner Type II processes, which have a narrower distribution of small varicosities with a mean diameter of only 1.4 +/- 0.6 microns (+/- SD, n = 214). Immunoelectron microscopy with peroxidase-labeled second antibody demonstrates that the varicosities are surrounded by a subsynaptic reticulum, that they contain immunoreactive vesicles of about 30–50 nm, and thus probably represent synaptic release sites. By iontophoretic application of glutamate we mapped the responsive sites on the muscle surface and found an excellent correspondence between transmitter sensitivity and the patterns of endings as described by immunocytochemistry. In contrast to our finding of numerous glutamate iontophoresis-sensitive sites, we did not detect any aspartate- responsive muscles. These data provide strong new evidence for glutamate being an endogenous transmitter at the Drosophila larval neuromuscular junction.